The Effect of Think-Pair-Share Technique to Improve Students’ Reading Comprehension on Narrative Text Text - Kurnianingsih, Intan; Isnaniah, Isnaniah (Foremost Journal, 2022)
This research is motivated by the lack of reading comprehension among students, which may be due to a lack of student motivation or the technique utilized in the learning process. Therefore, the researcher attempted to incorporate Think Pair Share into the learning process. This study tries to assess whether or not the Think-Pair-Share strategy has a substantial impact on students' reading comprehension. This study was conducted at SMA Syekh Yusuf Tangerang using samples from grade 2. This research is pre-experimental in nature. This study sampled two classes: XI IPS1 as the experimental class and XI IPS2 as the control class. Both groups were given a pre-test at the start of the study, various procedures in the middle, and a post-test at the conclusion. The acquired data were analyzed using version 24 of IBM SPSS statistics. Using the T-test, researchers assessed the test findings. The findings of the data analysis indicate that t count is more than t table (3,775>1,679), so Ha is approved. This indicates that Think Pair Share has a good effect on pupils' reading comprehension.